2004
DOI: 10.1099/mic.0.27121-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the dialysable serum inducer of germ-tube formation in Candida albicans

Abstract: Yeast cells of Candida albicans are induced by serum at 37 6C to produce germ tubes, the first step in a transition from yeast to hyphal growth. Previously, it has been shown that the active component is not serum albumin but is present in the dialysable fraction of serum. In this study, serum induction of germ-tube formation is shown to occur even in the presence of added exogenous nitrogen sources and is therefore not signalled by nitrogen derepression. The active component in serum was purified by ion-excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 42 publications
4
51
0
1
Order By: Relevance
“…However, deletion of either CDC25 or RAS1 affected the glucose-and serum-induced cAMP signal, consistent with mediation of the glucoseinduced cAMP increase in C. albicans by the Cdc25-Ras1 branch of the glucose response pathway and probably not via the Gpr1-Gpa2 branch (193). Addition of serum results in a rapid response, similar to that seen with glucose, supporting a recent finding that glucose is the main factor in serum affecting Candida morphogenesis (135). Two important gaps remain in our understanding of the upstream components of the cAMP-PKA pathway in C. albicans: (i) the identity of the receptor activating the Cdc25 guanine nucleotide exchange protein and (ii) the nature of the ligand for Gpr1.…”
Section: Camp-pka Pathwaysupporting
confidence: 67%
“…However, deletion of either CDC25 or RAS1 affected the glucose-and serum-induced cAMP signal, consistent with mediation of the glucoseinduced cAMP increase in C. albicans by the Cdc25-Ras1 branch of the glucose response pathway and probably not via the Gpr1-Gpa2 branch (193). Addition of serum results in a rapid response, similar to that seen with glucose, supporting a recent finding that glucose is the main factor in serum affecting Candida morphogenesis (135). Two important gaps remain in our understanding of the upstream components of the cAMP-PKA pathway in C. albicans: (i) the identity of the receptor activating the Cdc25 guanine nucleotide exchange protein and (ii) the nature of the ligand for Gpr1.…”
Section: Camp-pka Pathwaysupporting
confidence: 67%
“…For decades, the component of serum responsible for triggering morphogenesis remained elusive. For some time, the glucose in serum was suggested to be responsible for morphogenesis (243); however, it was recently shown that bacterial peptidoglycans in serum trigger hyphal growth by directly activating the adenylyl cyclase Cyr1 (635). RPMI and M199 media also stimulate yeast-to-hypha morphogenesis at elevated temperatures and are thought to act through a common pathway with serum.…”
Section: Environmental Signals That Regulate Morphogenesismentioning
confidence: 99%
“…Early work suggested that serum had a lethal effect on C. albicans and that this activity was heat stable and dialyzable (30), but it was later demonstrated that the reduced numbers of CFU measured by these experiments were attributable to increased aggregation of Candida cells rather than to a lethal effect of serum (10). This serum-induced aggregation is related to serum stimulation of the yeast-tohypha transition, and though the search for the switching stimulus in serum has been one of the most enduring questions in Candida pathogenesis (4,17,25,36,46), no obvious culprit has been definitively identified yet. Recent studies reveal that serum does become profoundly toxic to C. albicans when calcineurin is either inhibited or mutated (7,44), findings reminiscent of the early C. albicans-serum work.…”
mentioning
confidence: 99%